Iodine and goitrogens distribution in drinking water of some secondary schools of Kebbi, Nigeria (GUB Journal of Science and Engineering, 2024)
The objective of this paper is to carry out an evaluation of iodine, calcium, magnesium, and other goitrogenic factors in drinking water obtained from three schools in Kebbi Local Government Area, Kebbi State, Nigeria. Standard methods and procedures including atomic absorption spectroscopy were utilized to attain the objective of the study. One-way analysis of variance (ANOVA) test was carried out and results are significant at (p¡0.05). The amounts of iodine, magnesium, phosphate, and calcium were in the ranges of 0.250 ± 0.02 - 0.120 ± 0.03 ppm, 2.2 ± 0.01- 10.0 ± 0.01 ppm, 0.03 ± 0.0001 -0.07 ± 0.0001 ppm, 3.4 ± 0.01 - 8.5 ± 0.01 ppm. There were diverse levels of the studied goitrogens. Fluoride, bromide, chloride, cyanide, perchlorate, and nitrate are in respective ranges as follows: 1.12 ± 0.02 - 3.14 ± 0.02 ppm, 0.02 ± 0.002 - 0.15 ± 0.002 ppm, 0.61 ± 0.002 - 1.21 ± 0.02 ppm, 0.32 ± 0.001 - 0.51 ± 0.001 ppm, 0.120 ±0.0001- 0.250±0.02 ppm, and 2.2±0.02 – 10.0±0.01 ppm respectively. The result has revealed that the water used in the studied schools contains goitrogens that can contribute to the interference in iodine metabolism and leading to consequent harmful effects on youngsters.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 9(1), 2022 P 23-29